Advances in Tracheal Intubation - Lovich-Sapola, Jessica A.; Lebak, Kelly; Bassett, Michael D.; Rubin, Kasia P. (IntechOpen, 2023)
Tracheal intubation is a common medical procedure. It is relatively simple to accomplish, although there are cases in which tube placement is difficult or even impossible. This book provides a comprehensive overview of endotracheal tube placement with chapters on advanced techniques, ultrasound use for airway management, airway management techniques for obstetric patients, and much more.